UNLOCK YOUR ENTREPRENEURIAL FUTURE: MASTERING SHOPEE AFFILIATE FOR SUCCESS - Pratesa, Dimas Putri Mega; Rahma, Adelia; Anfi, Dieva (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2025)
Digital entrepreneurship is increasingly becoming the main focus of economic development, especially in the era of rapid digitalization. The training aims to explore strategies and best practices in the Shopee affiliate program to support entrepreneurial success with presentation methods, interactive discussions, and case studies. The training results show that Shopee's affiliate program not only increases the revenue potential for affiliates but also contributes to improving entrepreneurial skills among students and business startups. The conclusion of this training emphasizes the importance of a deep understanding of digital marketing and the development of entrepreneurial skills to take advantage of the opportunities offered by platforms like Shopee. In the future, it is expected to guide individuals who want to maximize their business potential through affiliate programs.